Covalent triazine-based frameworks with cobalt-loading for visible light-driven photocatalytic water oxidation. Issue 17 (2nd August 2022) - Chen, Hongmei; Gardner, Adrian M.; Lin, Guoan; Zhao, Wei; Bahri, Mounib; Browning, Nigel D.; Sprick, Reiner Sebastian; Li, Xiaobo; Xu, Xiaoxiang; Cooper, Andrew I.
Abstract : Incorporating Co through the bipyridine coordination sites within CTF results in rapid charge-separation, thus improving the photocatalytic water oxidation performance. Abstract : Conjugated polymers have received significant attention as photocatalysts. However, photocatalytic oxygen evolution has only been reported for a few polymers so far. Here, we present a bipyridine based covalent triazine-based framework containing metal coordination sites (Bpy-CTF). The material is highly active for sacrificial photocatalytic oxygen evolution with a rate of 322 μmol g −1 h −1 under visible light illumination (≥420 nm) after post-synthetic cobalt coordination. An analogous photocatalyst containing biphenyl was found to be less active as it is not able to coordinate cobalt. Transient absorption spectroscopy studies showed that the cobalt coordinated in the bipyridine units of Bpy-CTF promotes charge separation and transfer, thus increasing water oxidation activity. The study demonstrates the growing potential of polymer photocatalysts for oxygen evolution by structural engineering and post-synthetic metalation.